Personal Augmented Reality Interior Design Assistant (PARIDA) - Raveendran, Ranju (Auckland University of Technology, 2021)
Personal Augmented Reality Interior Design Assistant (PARIDA) – a guided interior designing application with the help of Augmented Reality (AR). The interaction between the person living in a space and the building is the basis of interior design. Colour selection, door handle choice, look and feel of areas where people touch/interact, general traffic in the house, light, and airflow, and even acoustic conditions are all factors to consider. An interior designer is trained to take all of these factors into account including the overall layout and size of the home when designing a suitable interior space for the people who will be living there. However, not everyone can afford an interior designer, and it is impractical to bring in and experiment with various types of home décor before finalising on a suitable one. This is where computer graphics can be useful. Recent advances in 3D computer graphics technology, such as Augmented Reality (AR) and Virtual Reality (VR), can be useful as a pre-visualisation tool for architecture and interior design. An AR app that runs on a mobile device is portable and does not require any additional hardware. Although there are a variety of AR applications aimed at interior design, a feature review revealed that those applications have little to no guidance system to assist the user in making decisions. PARIDA is an augmented reality application that aims to fill this gap by guiding a novice user through the process of designing high-quality interiors. Professional interior designers may find it useful to easily prototype their designs and make accurate judgments before installation. Home décor stores may find it useful to assist their customers in determining which product will best suit their needs.
Keywords: Augmented Reality; Virtual Reality; Interior Design; Mobile Application; ARCore; UI/UX; Unity3D; ARFoundation; Design Styles